1999
DOI: 10.1006/jipa.1998.4798
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contaminants and the Prevalence of Hemic Neoplasia (Leukemia) in the Common Mussel (Mytilus edulisComplex) from Puget Sound, Washington, U.S.A.

Abstract: The relationship between hemic neoplasia, a blood cell disorder in bivalve molluscs, and chemical contaminants was evaluated in the common mussel (Mytilus edulis complex). Hemic neoplasia (HN) is endemic to mussel populations in Puget Sound. The prevalence of hemic neoplasia ranged from 0 to 30% in mussels from nine sites in Puget Sound, Washington. Organic chemical contamination in sediment from these sites range from 0.1 to 64.0 ppm of polycyclic aromatic hydrocarbons (PAHs) and 0.07 to 0.50 ppm chlorinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Other authors (Krishnakumar et al, 1999) were unable to link chemical exposure to onset of haemic neoplasia. We and others have demonstrated that the p53 gene and its family member, p73, are implicated in the onset of molluscan leukemia (Barker et al, 1997;Kelley et al, 2001;Stephens et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Other authors (Krishnakumar et al, 1999) were unable to link chemical exposure to onset of haemic neoplasia. We and others have demonstrated that the p53 gene and its family member, p73, are implicated in the onset of molluscan leukemia (Barker et al, 1997;Kelley et al, 2001;Stephens et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Neoplasms in C. edule were initially recorded in 1982 in Cork Harbour, Ireland, and in that same year they were also reported in Brittany, France (Twomey & Mulcahy 1988, Twomey 1994, Villalba et al 2001, Romalde et al 2007, Le Grand et al 2010. Disseminated neoplasia is a proliferative disorder of the haemocytes and is of unknown origin; it is characterised by very large, mitotically active, pleomorphic and highly invasive cells (Twomey 1994, Krishnakumar et al 1999, Collins & Mulcahy 2003, Barber 2004, Ciocan et al 2006, Le Grand et al 2010, Díaz et al 2011.Throughout their range Cerastoderma edule are known to act as the first or second intermediate host for at least 16 digenean parasites from 7 different families, of which the family Echinostomatidae is the most dominant (de Montaudouin et al 2009). A recent study along the southwest coast of Ireland found 8 species of digenean parasites in C. edule, and Meiogymnophallus minutus (synonym Parvatrema minutus, Scholz 2002) was the most common in terms of prevalence and intensity of infection (Fermer et al 2009).…”
mentioning
confidence: 99%
“…To determine the prevalence of HN, 0.2-0.5 ml of hemolymph was drawn from the posterior adductor muscle of 20 mussels per month per site. Hemolymph was collected with a 23-gauge needle into a 3-cc syringe containing 0.5 ml Tris-EDTA hemocyte buffer (Krishnakumar et al 1999). The contents of the syringe were then placed on a poly-L-lysine slide in a moist chamber and incubated at room temperature for 30 min.…”
Section: Biologymentioning
confidence: 99%